A Comparative Experimental Investigation Between the Mineral Oil and Vegetable Oil-Based Mono Nanofluids for Transformer Application - Syarafi Shuhaimi M.; Vicki Wanatasanappan V. (Springer Science and Business Media Deutschland GmbH, 2024)
Throughout the process of transmitting the electrical energy, losses continuously tend to occur in the transformer in the form of heat. Therefore, insulating and cooling oil is required to increase to maintain the temperature of power transformers. Coolants are introduced into the transformer to carry out the cooling process. Usually, conventional mineral oil is commonly applied as a cooling liquid for the transformer. However, it is believed that traditional mineral oil is a highly flammable liquid and lacks biodegradability. Thus, palm oil and palm oil/ZnO nanofluid are introduced to overcome the limitations of conventional mineral oil. This research aims to evaluate the effect of nanoparticle volume concentration on the thermal conductivity, dynamic viscosity and dielectric strength of palm oil/ZnO-based nanofluid by an experimental comparison with mineral oil at different temperatures. The samples prepared are conventional mineral oil, pure palm oil and palm oil nanofluid with ZnO at concentrations of 0.05, 0.15 and 0.25%. The breakdown voltage and thermal conductivity results show that pure palm oil and palm oil/ZnO nanofluid give enhanced results compared to conventional mineral oil. However, the viscosity properties, which represent the resistance for the coolant to circulate around the transformer, prove that conventional mineral oil has the lowest viscosity of other samples. Palm oil suspended with ZnO nanoparticles has good potential to be used as insulating oil in transformers. 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.